2022
DOI: 10.1007/s11269-022-03084-6
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Residual and Hidden Potential for Small and Micro Hydropower in Europe? A Screening-Level Regional Assessment

Abstract: Small hydropower plants (installed power below 10 MW) are generally considered less impacting than larger plants, and this has stimulated their rapid spread, with a developing potential that is not exhausted yet. However, since they can cause environmental impacts, especially in case of cascade installations, there is the need to operate them in a more sustainable way, e.g. considering ecosystem needs and by developing low-impacting technologies. In this paper, an assessment was conducted to estimate how the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…It was ensured that the students themselves were able to realize that their own development is closely related to the future of the country to be responsible for themselves, for society and for their families. Thus they could enter socialism with Chinese characteristics on their own under the leadership of the Communist Party of China and meet the basic requirements for the great rejuvenation of the Chinese nation, so that the teaching staff and the students could firmly believe in and establish common ideals and realize the guidance of self-awareness [ 10 ] Yu, et al found that it was in this context that Marxist beliefs could be strengthened. Students could develop holistically within higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was ensured that the students themselves were able to realize that their own development is closely related to the future of the country to be responsible for themselves, for society and for their families. Thus they could enter socialism with Chinese characteristics on their own under the leadership of the Communist Party of China and meet the basic requirements for the great rejuvenation of the Chinese nation, so that the teaching staff and the students could firmly believe in and establish common ideals and realize the guidance of self-awareness [ 10 ] Yu, et al found that it was in this context that Marxist beliefs could be strengthened. Students could develop holistically within higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of mini hydropower plants (< 1 MW) are not covered by the database; nevertheless, power plants below 1 MW represent 3 GW of the EU hydropower fleet (1.9%) 24 , of which a negligible share is represented by unconventional turbines, e.g. water wheels, Archimedes screws and Very Low Head (VLH) turbines.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroelectric power has also been evaluated as a potential renewable energy source in urban areas. Micro-hydropower systems can be installed in urban areas to generate electricity from small streams or water sources (Boroomandnia et al, 2022;Quaranta et al, 2022). The study suggested that micro-hydropower systems could be used to power street lights, tra c signals, and other public infrastructure, reducing the dependence on grid power and improving the reliability of power supply.…”
Section: Literature Reviewmentioning
confidence: 99%